Reach and effectiveness of a HEARTS hypertension pilot project in Guatemala - Irmgardt Alicia Wellmann; José Javier Rodríguez; Benilda Batzin; Guillermo Hegel; Luis Fernando Ayala; Kim Ozano; Meredith P. Fort; Walter Flores; Lesly Ramirez; Eduardo Palacios; Mayron Martínez; Manuel Ramirez-Zea; et al. (Revista Panamericana de Salud Pública)
The World Health Organization Global Hearts initiative (HEARTS) and technical package aim to improve the primary health care management of hypertension and other risk factors for cardiovascular disease at the population level. This study describes the first HEARTS implementation pilot project in Guatemala’s Ministry of Health (MOH) primary health care system. This pilot began in April 2022 in six primary health care facilities in three rural indigenous municipalities. The project consisted of HEARTS-aligned strategies adapted to enhance program sustainability in Guatemala. Outcomes were defined using the Reach, Effectiveness, Adoption, Implementation, Maintenance (RE-AIM) framework. The primary reach outcome was treatment count, defined as the absolute number of patients per month receiving medication treatment for hypertension. The primary effectiveness outcomes were mean systolic blood pressure (BP), mean diastolic BP, and proportion of patients with BP control (<130/80 mmHg). In the first month of the post-implementation period, there was a statistically significant increase of 25 patients treated per month above the baseline of 20 to 25 patients (P = .002), followed by a significant increase of 2.4 additional patients treated each month (P = .005) thereafter. The mean change in systolic BP was −4.4 (95% CI, −8.2 to −0.5; P = 0.028) mmHg, and the mean change in diastolic BP was −0.9 (95% CI, −2.8 to 1.1; P = .376) mmHg. The proportion of the cohort with BP control increased from 33.4% at baseline to 47.1% at 6 months (adjusted change, 13.7%; 95% CI, 2.2% to 25.2%; P = .027). These findings support the feasibility of implementing the HEARTS model for BP control throughout the MOH primary health care system, which is where most Guatemalans with hypertension seek care.